2015
DOI: 10.1039/c5fo00715a
|View full text |Cite
|
Sign up to set email alerts
|

The ex vivo antiplatelet activation potential of fruit phenolic metabolite hippuric acid

Abstract: Polyphenol-rich fruit and vegetable intake has been associated with reduction in platelet hyperactivity, a significant contributor to thrombus formation. This study was undertaken to investigate the possible role of hippuric acid, a predominant metabolite of plant cyclic polyols, phenolic acids and polyphenols, in reduction of platelet activation-related thrombogenesis. Fasting blood samples were collected from 13 healthy subjects to analyse the effect of varying concentrations of hippuric acid (100 μM, 200 μM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Similar findings were obtained for hippuric acid, the predominant metabolite of some phenolic acids and polyphenols, which reduced platelet aggregation and P‐selectin/CD62P expression at 1–2 mM. Hippuric acid, however, is actively excreted from the body with maximal plasma concentrations of ~200–300 μM (Santhakumar et al , ). Meanwhile, pelargonidin aglycone, but not the glucoside adduct, inhibited thrombin‐induced fibrin polymerization and platelet aggregation and elicited anticoagulant effects in mice.…”
Section: Polyphenols As Pharmacological Agentssupporting
confidence: 61%
“…Similar findings were obtained for hippuric acid, the predominant metabolite of some phenolic acids and polyphenols, which reduced platelet aggregation and P‐selectin/CD62P expression at 1–2 mM. Hippuric acid, however, is actively excreted from the body with maximal plasma concentrations of ~200–300 μM (Santhakumar et al , ). Meanwhile, pelargonidin aglycone, but not the glucoside adduct, inhibited thrombin‐induced fibrin polymerization and platelet aggregation and elicited anticoagulant effects in mice.…”
Section: Polyphenols As Pharmacological Agentssupporting
confidence: 61%
“…Numerous studies have already shown the ability of free radicals (O2 -, H2O2, NADPH Oxidase; NOX) to increase cellular adhesion molecules such as P-selectin, PCAM, E-selectin and VCAM-1 on platelet and endothelial cell surfaces. P-Selectin is a cellular adhesion molecule released from activated platelet and endothelial cells; it is known to play a key role in leukocyte recruitment and the formation of large thrombus [19,20]. Similarly E-Selectin, an endothelial-leukocyte adhesion molecule, is overexpressed under elevated oxidative stress and inflammatory states.…”
Section: Major Pathways Leading To Cardiovascular Diseasementioning
confidence: 99%
“…Endothelial expression of these adhesion molecules plays a major role in platelet aggregation and the atherogenesis. Studies have shown that with the increase in expression of P-Selectin and E-Selectin, elevated platelet-fibrin and plateletleukocyte aggregation ensues thrombogenic activity [19]. The elevated ICAM-1 and VCAM-1 at the endothelial cell also contribute to the increased state of platelet aggregation and adhesion.…”
Section: Cellular Adhesion Molecules and Endothelial Dysfunctionmentioning
confidence: 99%
“…Moreover, a review of 97 bioavailability studies showed that plasma concentrations and urinary excretion differ depending on the type and not the proportion of polyphenols in the diet. Due to such important parameters associated with bioavailability, it has been suggested that the metabolites of polyphenols should rather be used to study antiplatelet effects [52,58,102].…”
Section: Evaluation Of Methods Used For Polyphenol Antiplatelet Studiesmentioning
confidence: 99%